2012
DOI: 10.5535/arm.2012.36.5.729
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatments on Patients with Anterior Cervical Hyperostosis-Derived Dysphagia

Abstract: Anterior cervical hyperostosis may be a cause of dysphagia. For anterior cervical hyperostosis, medical or surgical treatments can be adhibited in view of the causative mechanisms and intensities of dysphagia. We report 3 cases of cervical hyperostosis-derived progressive dysphagia that underwent operation. Radiologic diagnosis and Video Fluoroscopic Swallowing Study were performed on the three patients for evaluation. One had history of recurrent aspiration pneumonia accompanied by weight loss, another compla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 10 publications
1
26
0
1
Order By: Relevance
“…The most frequent bibliographic records found in the medical literature link these clinical pictures to Forestier's disease or diffuse idiopathic skeletal hyperostosis [6][7][8][9][10] and to a lesser degree, with osteophytes of arthrotic origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent bibliographic records found in the medical literature link these clinical pictures to Forestier's disease or diffuse idiopathic skeletal hyperostosis [6][7][8][9][10] and to a lesser degree, with osteophytes of arthrotic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Resection should be performed through an anterior route with the usual approach, resecting the osteophyte with a chisel, rongeurs or drill. Miyamoto et al (10) demonstrated that if we perform the resection of an anterior vertebral cervical osteophyte, it can be regenerated with average growth of 1 mm per year.…”
Section: Discussionmentioning
confidence: 99%
“…1 지속적인 연하곤란은 음식물의 흡인에 의한 기침과 고령에서 폐렴의 합병증을 유발 할 수 있다. 2,3 구인두 연하곤란을 일으키는 구조적 원인 중 경추 전방 골극 이 인두, 상부식도, 상부기도를 직접적으로 압박하거나 주변의 근육의 수축을 일으켜 연하곤란 및 구강의 음식물이 기도로 흡 인되어 조절이 되지 않은 기침, 흡인성 폐렴 및 드물게는 폐쇄 성 수면 무호흡증, 발성장애를 유발하는 합병증과 연관된 보고 들이 있었다. [2][3][4][5] 진단은 (Fig.…”
Section: 서 론unclassified
“…This condition can cause dysphagia due to pressure on the posterior aspect of the esophagus. Cases of dysphagia caused by hypertrophic anterior cervical osteophytes have been increasing in number in the literature in recent years [ 7 8 9 10 ]. Dysphagia caused by neurological disorders is mostly seen in patients suffering from diffuse idiopathic skeletal hyperostosis (DISH) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%